Power, Powerlessness, and Globalization : Contemporary Politics in the Global South - Agyeman, Opoku, 1942- (Lexington Books, 2014)
This book examines the historical forces that have shaped contemporary politics in the Global South, drawing from events in Asia, Latin America, and Africa. It provides insights on internal political processes and the international system and contributes an elemental theory of political development.